Early prognosticators of later TSPO-PET-measurable microglial activation in multiple sclerosis - Laaksonen Sini; Saraste Maija; Sucksdorff Marcus; Nylund Marjo; Vuorimaa Anna; Matilainen Markus; Heikkinen Jaakko; Airas Laura (ELSEVIER SCI LTD, 2025)
Background: Factors driving increased innate immune cell activation in multiple sclerosis (MS) brain are not well understood. As higher prevalence of microglial/macrophage activation in association with chronic lesions and diffusely in the normal appearing white matter predict more rapid accumulation of clinical disability, it is of high importance to understand processes behind this. Objective of the study was to explore demographic, clinical and paraclinical variables associating with later positron emission tomography (PET)-measurable innate immune cell activation.
Methods: PET-imaging using a TSPO-binding [11C]PK11195 was performed to evaluate microglial activation in patients with relapsing-remitting MS aged 40-55 years with a minimum disease duration of five years (n = 37). Medical records and diagnostic MR images were reviewed for relevant early MS disease-related clinical and paraclinical parameters.
Results: More prominent microglial activation was associated with higher number of T2 lesions in the diagnostic MRI, a higher immunoglobulin G (IgG) index in the diagnostic CSF and Expanded Disability Status Scale (EDSS) >= 2.0 five years after diagnosis.
Conclusion: The number of T2 lesions in MRI, and CSF immunoglobulin content measured by IgG index at the time of MS diagnosis associated with later TSPO-PET-measurable innate immune cell activation. This suggests that both focal and diffuse early inflammatory phenomena impact the development of later progression-related pathology.